Ethnographic elements in the 16th century Peruvian soldiery chronicle: The vision of the other - Stoll, Eva (2012)
The Spanis conquerors form an important group of authors within the historiographical context of the colonial world. The object of this article is to focus on the question how the indigenous people are described in the chronicles written by soldiers, which kind of motives, arguments and discourse traditions predominate in their ethnographical representation. Three Peruvian soldiers-chronicles of the sixteenth century will be analyzed in this perspective: the Memoria written by Juan Ruiz de Arce [ca. 1543], the Relacion del descubrimiento y conquista de los reinos del Perú [ca. 1565] by Alonso Borregán. It is to be shown that these texts not only differ in their degree of accuracy, but also in different kinds of instrumentalization of the ethnographic discourse.